The innovative posture of SMEs depending on the usage of marketing tools - Ključnikov, Aleksandr; Civelek, Mehmet; Chovanová Supeková, Soňa (Serbian Journal of Management, 2022)
Although SMEs have quick adaptions to new trends, most of them suffer from having lack of financial and human resources. This fact has made those businesses disadvantaged in the usage of traditional marketing tools compared to their larger rivals. Information and communication technologies and the developments in technology-based platforms have also provided less costly but more innovative marketing options for SMEs to compete with their larger counterparts. In this regard, this research purposes of examining the impacts of the usage of traditional and technology-enabled marketing tools by SMEs on their innovativeness. In parallel with this selected purpose, the researchers have gained data from 812 SMEs in Slovakia by employing an online internet-mediated questionnaire. The researchers also apply Binary Logistic Regression Test to analyze the impacts of traditional and technology-enabled marketing tools on the innovativeness of SMEs. The results show that while usage of technology-enabled marketing channels positively affects the innovativeness of firms, the usage of traditional marketing channels by SMEs does not affect their innovativeness. Environmental, resource-related, and personal factors might be the reasons of these results.